Ultrasound Shear Wave Elastography of Normal Pancreas in Adult Subjects - Shayeri Roy Choudhury; Mansi Verma; Pankaj Gupta; Harjeet Singh; Vishal Sharma; Rakesh Kochhar (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Background and Purpose Transabdominal ultrasound (US)-based shear wave elastography (SWE) provides an attractive method of estimating pancreatic stiffness. There is limited data on the SWE values of the healthy pancreas in Indian subjects. The current study aimed to evaluate SWE of the normal pancreas. Methods We performed a study from January 2019 to March 2019. We included adult patients who presented for the US of the upper abdomen for vague abdominal symptoms, unrelated to the pancreas. The SWE values were obtained from the pancreatic head and body. The association of pancreatic SWE with age, gender, fatty liver, chronic liver disease, and cholelithiasis was recorded. Results During the study period, 205 subjects underwent SWE of the pancreas. The mean age of subjects was 41.3 (standard deviation [SD] 15.3) years. There were 93 males and 112 females. The mean SWE value in the head of the pancreas was 8.98 (SD 2.46 kPa), and that in the body region was 8.67 (SD 2.67 kPa). There was a positive correlation of SWE with age. The SWE of the pancreatic body was significantly higher in patients who had a fatty liver on US (p < 0.05). There was no significant association of SWE of the pancreas with gender, presence of chronic liver disease, or gallstones. Conclusion The normal values of pancreatic SWE are correlated with age and fatty change in the liver.